PENINGKATAN KEMAMPUAN KONEKSI MATEMATIS SISWA MELALUI PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION DAN TEAM GAMES TOURNAMENT - Manik, Selfrima Hadinyata; Saija, Louise (LPPM Universitas Advent Indonesia, 2019)
Abstract: Mathematical connection skills is the ability of students to connect mathematics itself, mathematics with other subjects, and mathematics with problems in daily life. This comparative research aims to compare students' mathematical connection skills through cooperative model the Cooperative Integrated Reading and Composition (CIRC) type and the Teams Games Tournament (TGT) type. The sample for this research was students in two classes in SD Kartika X-3 Parongpong, namely class III B , and class III C. The instruments used is a test of mathematical connection skills that consists of a subjective question about the two- dimensional figure topic, and a non-test instruments in the form of student response questionnaires. The results showed that: The increase in mathematical skills of students who obtained the cooperative learning model Cooperative Integrated Reading and Composition (CIRC) type and the Teams Games Tournament (TGT) type are in the high category, but there is no significant difference in the increase in students' mathematical connection skills between the two learning models. Next, the results of the Student responses questionnaire indicate that students like the cooperative learning model Cooperative Integrated Reading and Composition (CIRC) type and the Teams Games Tournament (TGT) type that they obtain. Keywords: Mathematical connection skills, Cooperative Integrated Reading and Composition (CIRC), Teams Games Tournament (TGT)